Low frequency of septic arthritis after arthrocentesis and intra-articular glucocorticoid injection. (3rd September 2019) - Petersen, SK; Hansen, IMJ; Andreasen, RA
Abstract : Objective : The aim of this study was to evaluate the risk of septic arthritis (SA) in patients who received an intra-articular (IA) glucocorticoid (GC) injection and to describe the characteristics of these patients. Methods : All patients undergoing IA procedures at the orthopaedic and rheumatological departments on the Danish island of Funen from January 2006 to December 2013 were identified in the central database and included by register extraction. Patients who developed a clinically inflamed joint and positive synovial fluid culture within 14 days after IA GC injection were considered as having SA. Retrospectively, data on age, gender, affected joint location, bacterial agent, pre-existing inflammatory disorder, and death within 30 days were extracted from the patient files. According to local recommendations, a non-touch sterile technique was used for IA procedures. Patients were informed about the risk of SA and advised to seek medical attention on suspicion of infection or lack of improvement. Results : In total, 22 370 IA procedures were performed. Among these, 14 118 GC injections and 8252 arthrocenteses were undertaken. Only 11 patients were diagnosed with SA (0.08%, 95% confidence interval 0.03–0.12). Risk factors for SA were male gender, age, and pre-existing joint disease. Conclusion : We found a low frequency of SA subsequent to IA GC injections. Older patients with pre-existing joint disease are at higher risk of developing SA.